Synthesis of CIS (CuInSe2) Based Materials for Solar Applications - Soydan, Ali Murat; Yilmaz, Pinar; Tunaboylu, BahadJr (Hindawi Ltd, 2018)
Nanopowders of copper indium diselenide were produced with five different organic solvents: ethylenediamine, triethanolamine, oleylamine, oleic acid, and polyetheramine. We successfully synthesized pure CIS nanopowders at a temperature of 240 degrees C at three different durations of 10 h, 20 h, and 40 h with a one-step process. This shorter time method offers important cost advantages in manufacturing. Polyetheramine and oleic acid were used for the first time in literature for CIS synthesis in an autoclave.
Keywords: Solvothermal Synthesis; Thin-Film; Nanoparticles; Mechanism